2015
DOI: 10.1128/aac.01833-15
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Ceftaroline against Staphylococcus aureus Isolates Collected in 2012 from Latin American Countries as Part of the AWARE Surveillance Program

Abstract: The in vitro activities of ceftaroline and comparators, using broth microdilution, were determined against 1,066 Staphylococcus aureus isolates from hospitalized patients. Seventeen medical centers from Latin American countries contributed isolates. Methicillin-resistant S. aureus (MRSA) percentages ranged from 46% (Brazil) to 62% (Argentina). All methicillin-susceptible S. aureus (MSSA) isolates were susceptible to ceftaroline. Ceftaroline activity against MRSA varied with MIC 90 s of 0.5 (Venezuela) to 2 (Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
1
13
0
1
Order By: Relevance
“…Significantly, it is perhaps the drug's most important and distinguishing feature within the class of beta-lactams, its activity against MRSA, that has been met with the most skepticism. In particular, concerns over the appropriateness of the currently recommended dosage of 600 mg twice daily for the treatment of infections caused by S. aureus isolates with MIC values above the current EUCAST breakpoint of 1 mg/liter (14) have been raised, given that CPT MIC 90 values of 2 mg/liter for MRSA have been reported in certain countries within Europe, in Latin America, and in Asia (15)(16)(17)(18)(19)(20). These concerns have driven the initiation of additional clinical trials evaluating an increased frequency of administration (every 8 h) and an extension of the duration of the intravenous infusion of the drug from 1 to 2 h as a potential future mode of administration for infections caused by less susceptible organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, it is perhaps the drug's most important and distinguishing feature within the class of beta-lactams, its activity against MRSA, that has been met with the most skepticism. In particular, concerns over the appropriateness of the currently recommended dosage of 600 mg twice daily for the treatment of infections caused by S. aureus isolates with MIC values above the current EUCAST breakpoint of 1 mg/liter (14) have been raised, given that CPT MIC 90 values of 2 mg/liter for MRSA have been reported in certain countries within Europe, in Latin America, and in Asia (15)(16)(17)(18)(19)(20). These concerns have driven the initiation of additional clinical trials evaluating an increased frequency of administration (every 8 h) and an extension of the duration of the intravenous infusion of the drug from 1 to 2 h as a potential future mode of administration for infections caused by less susceptible organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Current treatment of critical S. aureus infections can be carried out by ceftaroline, a highly advanced β-lactam drug that received FDA approval in 2010. Several recent clinical surveillance studies however suggest that ceftaroline non-susceptibility in S. aureus is on the rise, which is mainly due to PBP2a point mutations [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, d-Ser also had sensitization activity in combination with ceftaroline. Ceftaroline, currently used as treatment of critical S. aureus infections, received FDA approval several years ago, now facing challenges that non-susceptible S. aureus is on the rise worldwide35., 36.. We studied and found that addition of 40 mmol/L d-Ser could enhance the antibacterial activity of ceftaroline against MRSA strains, with the MICs reduced by 2–16 times (data not shown).…”
Section: Discussionmentioning
confidence: 94%
“…Ceftaroline, currently used as treatment of critical S. aureus infections, received FDA approval several years ago, now facing challenges that non-susceptible S. aureus is on the rise worldwide 35. , 36. .…”
Section: Discussionmentioning
confidence: 99%